Essential Regulation of Spermatogonial Stem Cell Fate Decisions and Male Fertility by APBB1 via Interaction with KAT5 and GDF15 in Humans and Mice - Dai Zhou; Bang Liu; Lvjun Liu; Guangmin Liu; Fang Zhu; Zenghui Huang; Shusheng Zhang; Zuping He; Liqing Fan (Research)
Spermatogonial stem cells (SSCs) are essential for initiating and maintaining normal spermatogenesis, and notably, they have important applications in both reproduction and regenerative medicine. Nevertheless, the molecular mechanisms controlling the fate determinations of human SSCs remain elusive. In this study, we identified a selective expression of APBB1 in dormant human SSCs. We demonstrated for the first time that APBB1 interacted with KAT5, which led to the suppression of GDF15 expression and consequent inhibition of human SSC proliferation. Intriguingly, Apbb1−/− mice assumed the disrupted spermatogenesis and markedly reduced fertility. SSC transplantation assays revealed that Apbb1 silencing enhanced SSC colonization and impeded their differentiation, which resulted in the impaired spermatogenesis. Notably, 4 deleterious APBB1 mutation sites were identified in 2,047 patients with non-obstructive azoospermia (NOA), and patients with the c.1940C>G mutation had a similar testicular phenotype with Apbb1−/− mice. Additionally, we observed lower expression levels of APBB1 in NOA patients with spermatogenic arrest than in obstructive azoospermia patients with normal spermatogenesis. Collectively, our findings highlight an essential role of APBB1/KAT5/GDF15 in governing human SSC fate decisions and maintaining normal spermatogenesis and underscore them as therapeutic targets for treating male infertility.